Young Children and the Creation of a Digital Identity on Social Networking Sites: Scoping Review - Valeska Berg; Diana Arabiat; Evalotte Morelius; Lisa Kervin; Maggie Zgambo; Suzanne Robinson; Mark Jenkins; Lisa Whitehead (JMIR Publications, 2024)
BackgroundThere is limited understanding of the concept of the digital identity of young children created through engagement on social networking sites. ObjectiveThe objective of this scoping review was to identify key characteristics of the concept of digital identity for children from conception to the age of 8 years on social networking sites. MethodsThis scoping review was conducted using the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines. The key databases searched were EBSCO, Web of Science, ProQuest ERIC, and Scopus. Gray literature sources (National Grey Literature Collection, ProQuest Dissertations and Theses, and Google Scholar) were also searched to identify unpublished studies. Articles were selected if they were published in English and reported data on the digital identity of children in relation to social networking sites. ResultsThe key terms used in the literature were sharenting, followed by digital footprints and children's identities. Our study revealed 2 approaches to the creation of digital identity: social digital identity and performative digital identity. The articles in this review most commonly used the term sharenting to describe the behavior parents engage in to create digital identities for children on social networking sites. Motivations to post information about children differed among parents; however, the most common reasons were to share with friends and family and create digital archives of childhood photos, termed social digital identity. The second motivation was categorized as performative digital identity. The risk of digital kidnapping and identity theft associated with the creation of digital identities also influenced parents' behaviors. ConclusionsThe creation of a digital identity for children is an emerging concept. Our review develops a deeper understanding of sharenting behaviors that can be used to better support parents and their children in creating a digital identity with children and awareness of the potential future impact. We recommend that future studies explore the perspectives of children as key stakeholders in the creation of their digital identity.